Pengaruh Teknologi Black Soldier Fly dan Tampuk dalam Peningkatan Pemilahan Sampah di Sumber di Desa Bukit Raya - Wahyu Widyarsana, I Made; Faqih Mustafiq; Ariiq Dzakwan Gusto; Sarah Atthiyah Zaqi; Muhammad Azhar Lathif; Putri, Lina Kharina; Fardyanto (Jurnal Serambi Engineering, 2025)
Bukit Raya Village, Sepaku District, North Penajam Paser Regency is located in Ring 1 of the National Capital City (IKN). The village faces public health challenges due to population growth and significant environmental changes. The more population, the more important it is to maintain a sustainable environment, and waste is one of the focal points to achieve this goal. Pollution from waste cannot be separated from the activities of the community. The research was conducted to investigate the effect of applying appropriate technology BSF (Black Soldier Fly) and Tampuk (Tube for Compost) on efforts to improve waste sorting habits at the source. Educational activities and technical guidance can increase public understanding of the definition of waste, why waste needs to be managed, procedures for sorting waste, and how to manage waste at the source. FGD (Focus Group Discussion) with Bukit Raya Village and NGOs as waste managers provided information that waste management in Bukit Raya Village was not up to standard. Based on the results of participatory observation and scoring methods, it can be concluded that the presence of advanced treatment in the form of appropriate technology for BSF (Black Soldier Fly) and Tampuk (Tubes for Compost) cultivation will provide an increase of 4.4% in the 3rd week of September, 26.31% in the 4th week of September, 37.5% in the 1st week of October, and 100% in the 2nd week of October 2024.